2013
DOI: 10.1093/jac/dkt359
|View full text |Cite
|
Sign up to set email alerts
|

Differences in nevirapine biotransformation as a factor for its sex-dependent dimorphic profile of adverse drug reactions

Abstract: There was a sex-dependent variation in nevirapine biotransformation, particularly in the generation of the 12-hydroxy-nevirapine and 3-hydroxy-nevirapine metabolites. These data are consistent with the sex-dependent formation of toxic reactive metabolites, which may contribute to the sex-dependent dimorphic profile of nevirapine toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 64 publications
0
14
1
Order By: Relevance
“…While some studies report genderrelated differences in terms of virological and immunological response to HAART, others do not (Anderson, 2008;Carr et al, 2014;Dong et al, 2012;Marinho et al, 2013). In this study, we report of an over-representation of females (81%).…”
Section: Demographic Characteristicscontrasting
confidence: 50%
See 1 more Smart Citation
“…While some studies report genderrelated differences in terms of virological and immunological response to HAART, others do not (Anderson, 2008;Carr et al, 2014;Dong et al, 2012;Marinho et al, 2013). In this study, we report of an over-representation of females (81%).…”
Section: Demographic Characteristicscontrasting
confidence: 50%
“…2011) 0.31 0.07 N/A Ugandan (Mukonzo et al, 2009) 0.36 0.10 NA Ghanaian (Bains et al, 2013;Griese et al 1999) 0 that it could be due to differential drug biotransformation, fat content, and exogenous and endogenous hormonal expression differences in males and females (Bersoff-Matcha et al, 2001;Dong et al, 2012;Marinho et al, 2013). Expression of liver enzymes responsible for drug metabolism has also been shown to vary with gender and BMI (Antinori et al, 2001;Bersoff-Matcha et al, 2001).…”
Section: Anthropometry Data and Nvp Plasma Concentrationmentioning
confidence: 99%
“…Upregulation of Gstm3 may have significance in that previous investigators have shown reactive metabolites from SULT activation of 12-hydroxy NVP (Antunes et al 2010) to interact with and form haptens with GSTpi both in vitro and in NVP-treated patient's serum (Meng et al 2013), the suggestion here being that Gstm3 may also be a target for haptan formation and perhaps enzymatic inactivation in this model. There are numerous reports of reactive metabolites derived from NVP (Marinho et al 2014) and as evidenced by gene expression, key routes of reactive metabolite production were clearly dysregulated (Cyp3a4 and Cyp2b6) after NGN treatment, which exhibited fairly similar elevations in treatment with NVP alone. However, Sult1e1 was markedly increased in expression in the NGN group as compared with the NVP-alone group.…”
Section: Discussionmentioning
confidence: 95%
“…The female sex, a well-known risk factor for NVP-induced toxicity, is associated with higher SULT expression [4] and lower plasma levels of 12-hydroxy-NVP [3]. Interestingly, apolipoprotein A1 (ApoA1) increases SULT2B1 activity and ApoA1 synthesis is increased by NVP [5, 6].…”
mentioning
confidence: 99%
“…The higher ApoA1 levels in women might stabilize SULT2B1 [6]. This would explain the lower levels of 12-hydroxy-NVP [3] and the higher hepatotoxicity found in women, due to increased sulfonation of this metabolite. These data support a role for ApoA1 in the sex dimorphic mechanism leading to NVP-induced toxicity.…”
mentioning
confidence: 99%